Antioxidant network-based signatures cluster glioblastoma into distinct redox-resistant phenotypes - Yang, Yihan; More, Sanket; De Smet, Frederik; De Vleeschouwer, Steven; Agostinis, Patrizia (Frontiers in Immunology, 2024)
Aberrant reactive oxygen species (ROS) production is a hallmark of cancer. Cancer cells develop particular antioxidant networks to harness ROS for their growth and propagation. In this study, we established three distinct transcriptional co-expression networks and signatures (termed clusters C1, C2, and C3) with distinct antioxidative potential in glioblastoma (GBM) cancer cells. Functional analysis of each cluster revealed that C1 exhibits strong antioxidant properties, C2 is marked with a discrepant inflammatory trait and C3 was identified as the cluster with the weakest antioxidative capacity. Intriguingly, C2 exhibited a strong correlation with the highly aggressive mesenchymal subtype of GBM. Furthermore, this cluster holds substantial prognostic importance: patients with higher gene set variation analysis (GSVA) scores of the C2 signature exhibited adverse outcomes in overall and progression-free survival. In summary, we provide a set of transcriptional signatures that unveil the antioxidative potential of GBM, offering a promising prognostic application and a guide for therapeutic strategies in GBM therapy.